DYNAMICS OF THE 1800 14C YR BP CALDERA-FORMING ERUPTION OF KSUDACH VOLCANO, KAMCHATKA, RUSSIA - Andrews B.J.; Gardner J.E.; Tait S.; Ponomareva V.V.; Melekestsev I.V. (My University, 2007)
The 1800 14C yr BP Ksudach KS1 rhyodacite deposits present an opportunity to study the effects of caldera collapse on eruption dynamics and behavior. Stratigraphic relations indicate four Phases of eruption, Initial, Main, Lithic, and Gray. Well-sorted, reverse-graded pumice fall deposits overlying a silty ash compose the Initial Phase layers. The Main, Lithic, and Gray Phases are represented by pumice fall layers interbedded with pyroclastic flow and surge deposits (proximally) and co-ignimbrite ashes (distally). Although most of the deposit is <30 wt.% lithics, the Lithic Phase layers are >50 wt.% lithics. White and gray pumice are compositionally indistinguishable, however vesicle textures and microlite populations indicate faster ascent by the white pumice prior to eruption of the Gray Phase. The eruption volume is estimated as ∼8.5 km3 magma (dense rock equivalent) and ∼3.6 km3 lithics. Isopleth maps indicate mass flux ranged from 5–10×10^7 kg/s during the Initial Phase to >10^8 kg/s during the Main, Lithic, and Gray Phases. Caldera Collapse during the Lithic Phase is reflected by a large increase in lithic particles and the abrupt textural change from white to gray pumice; collapse began following eruption of ∼66% of the magma, and finished when ∼72% of the magma was erupted. Stratigraphic, granulometric, and component analyses indicate simultaneous eruption of buoyant plumes and non-buoyant flows during the Main, Lithic, and Gray Phases. Although mass flux did not change significantly following caldera collapse, the Gray Phase of eruption was dominated by non-buoyant flows in contrast to the earlier Phases that erupted mostly buoyant plumes.
Keywords: 38.37.25 Вулканология; Ксудач